Energy-Volume Coefficient and Limiting Excess Molar Volume Studies of Some Carbohydrates in Dilute Aqueous Solutions at 288.15 K - S. Dhondge, Sudhakar; Dhondge, Alka; J. Patil, Kesharsingh; A. Tomar, Preeti (Asian Journal of Chemistry, 2013)
In this work, we report the determination of energy volume coefficient also called as an internal pressure (Pint) in the dilute concentration region for the basic carbohydrates i.e., glucose, fructose, sucrose, galactose and lactose in aqueous solutions at 288.15 K in the concentration range 0-0.05 mol kg-1. To obtain this one requires precise isothermal compressibility and expansivity data. We used earlier reported data of density (r) and speed of sound (u) obtained at 278.15, 288.15 and 298.15 K; assuming specific heat (CP) is nearly the same in the studied concentration region. The internal pressure for solutions is found to increase with concentration of solute linearly and the increase depends upon the number of polar hydroxyl groups and conformational characteristics of the carbohydrate molecules. It is well known that apparent molar volumes of (fV) of these compounds do not vary with concentration in dilute solution region (almost ideal solutions), while the conformational specificity is reflected only in limiting partial molar volumes because of solute-solvent interactions. We applied Gibson-Tait equation of state to internal pressure data and obtained limiting excess molar volumes (V20E ) and found that values of excess molar volume of these compounds are highly negative (-31 × 10-6 to -62 × 10-6 m3 mol-1) at 288.15 K. These are large negative when compared with the molar volume data of solid carbohydrates. The differences are attributed to void volume and cage volume contribution to the total volume of solute molecule. It is invoked that when carbohydrates are dissolved in water, almost all free and void volumes are being used up due to dipole (-OH) and water molecular interactions through hydrogen bonding and retaining water structural characteristics intact in solution phase.